2018
DOI: 10.21608/jppp.2018.44104
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity of Certain Acaricides against Tetranychus urticae Koch and their Side Effects on Phytoseiulus persimilis A.-H. (Acari: Tetranychidae: Phytoseiidae)

Abstract: The acaricidal activity using the recommended concentrations of the novel compound cyflumetofen 24% SC as compared with bifenazate 48% SC and abamectine 1.8% EC was determined against the two-spotted spider mite, Tetranychus urticae Koch under greenhouse conditions at Faculty of Agriculture, Cairo University during 2017-2018. Their side effect on the predatory phytoseiid mite, Phytoseiulus persimilis Athias-Henriot was also investigated. Average number of mite mortality in the two seasons showed that abamectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Similar investigation study about prey and predator fitness under acaricide uses of control was for Abdel-Rahman and Ahmed [26] where in two-season experiment showed that abamectin was more toxic to the predatory mite, P. persimilis than other acaricides. While cyflumetofen was more toxic to spider mites T. urticae and followed by abamectin and bifenazate and in field trials cyflumetofen was not as harmful as other compounds.…”
Section: Demographic Analysis Of Treated P Persimilissupporting
confidence: 59%
“…Similar investigation study about prey and predator fitness under acaricide uses of control was for Abdel-Rahman and Ahmed [26] where in two-season experiment showed that abamectin was more toxic to the predatory mite, P. persimilis than other acaricides. While cyflumetofen was more toxic to spider mites T. urticae and followed by abamectin and bifenazate and in field trials cyflumetofen was not as harmful as other compounds.…”
Section: Demographic Analysis Of Treated P Persimilissupporting
confidence: 59%
“…Unfortunately, natural enemies are usually more susceptible to the toxic effect of the pesticides than their phytophagous preys owing to their lessdeveloped enzyme-based detoxification systems (Sato et al, 2002 andAkalach, 2006). Generally, IPM requires pesticides to be effective against target pests and, at the same time, to be relatively harmless to nontarget parasitic and predatory arthropods (Abdel Rahman and Fouly, 2001;Lee et al, 2002 andAhmed 2018). Most fungicides often have very subtle toxic effects on predaceous mites and they must be thoroughly evaluated before they are implemented in IPM programs (Bostanian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%